Analysis of Creative Thinking Skill and Student Learning Interest through Mind Mapping Based Creative Problem-Solving Learning Model - Meiarti, Devi; Wiyanto, Wiyanto; Yulianti, Ian (Physics Communication, 2020)
Creative thinking skill is one of the most important skills in the learning process in 21st century. Creative thinking skills influenced by student’s learning interest. Therefore, creative thinking and learning interest must be cultivated through a proper learning process. This research aims to analyze student’s creative thinking skills and learning interest through mind mapping-based creative problem solving learning models. This research method used mixed methods with a sequential explanatory design. The population of this research was all students of class X with 30 students as the sample. The instrument used an essay test for creative thinking, an interview sheet, and learning interest questionnaire. The results of the n-gain alalysis showed an increase for each indicator of the creative thinking skills with an average of 71.73 included in the high criteria. As for the percentage of student’s learning interest is 79.17% which is included in good criteria. The results of the interview showed that there was different creative thinking patterns for each category where students in solving problems tended to begin by understanding the problem, linking scientific theory with their own knowledge, then developing it based on experience and reasoning. However, seen from the answers and interview results, students with very high creative thinking skills are better at providing ideas or conclusions than students with high, medium, and low categories. The results of the correlation analysis showed that there was a positive and significant relationship between student’s learning interest and four indicators of creative thinking skills.